Invitation to First Poly Royal in 1933 (1933)
An invitation to the first Poly Royal in 1933. This was the first year the phrase 'Poly Royal' was used to refer to the annual celebration and showcase previously known as Farmer's Picnic. This was also the year the celebration returned after a ten year span of time when lack of funding prevented Farmer's Picnic from taking place.